Distinctive properties of biological neural networks and recent advances in bottom-up approaches toward a better biologically plausible neural network - Jeon, Ikhwan; Kim, Taegon (Frontiers in Computational Neuroscience, 2023)
Although it may appear infeasible and impractical, building artificial intelligence (AI) using a bottom-up approach based on understandings of neuroscience is straightforward. The lack of a generalized governing principle for biological neural network forces us to address this problem by converting piecemeal information on the diverse features of neurons, synapses, and neural circuits into AI. In this review, we described recent attempts to build a biologically plausible neural network by following neuroscientifically similar strategies of neural network optimization or by implanting the outcome of the optimization, such as the properties of single computational units and the characteristics of the network architecture. In addition, we proposed a formalism of the relationship between the set of objectives that neural networks attempt to achieve and neural network classes categorized by how closely their architectural features resemble those of BNN. This formalism is expected to define the potential roles of top-down and bottom-up approaches for building a biologically plausible neural network, and offer a map helping the navigation in the gap between neuroscience and AI engineering.